MEMPREDIKSI KINERJA KEUANGAN DENGAN MODAL INTELEKTUAL PADA PERUSAHAAN PERBANKAN TERBUKA DI BURSA EFEK JAKARTA - Sri Iswati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
To overcome the competition, a company not only focuses on physical capitals, but also focuses on intellectual capitals. Company can achieve a competitive advantage and earn profit by owing intellectual capitals. Intellectual capitals rest on a potential link between intellectual capitals on one hand and corporate performance on the other hand. A company will grow up if a growing number of physical capitals in the same line with a growing number of intellectual capitals.The purpose of this empirical study is to investigate the influence of intellectual on bank performance, especially financial performance. This study uses empirical data from Indonesia Capital Market Directory 2005 issued by Jakarta Stock Exchange (JSE). This research uses quantitative analysis. The population of the research are banks listed in JSE. The hypothesis test uses regression analysis model with the degree of significance at 0.05. The main conclusion of this particular study is intellectual capitals have no influence on bank performance.